Synthesis and Electrical and Gas Sensing Properties of Some 5-(Quinolinylmethylene)-2-thioxodihydropyrimidine-4,6(1H,5H)-dione and 5-(Quinolinylmethylene)pyrimidine-2,4,6(1H,3H,5H)-trione Derivatives - Beker, H. Kerim; Canlica, Mevlude; Akinci, Alper; Altindal, Ahmet; Kaban, Seniz (HINDAWI LTD, 2013)
Eight new 5-(quinolinylmethylene)barbituric acid derivatives were synthesized by the reaction of 1,3-dimethylbarbituric acid and 1,3-diethyl-2-thiobarbituric acid with quinoline-4-carboxaldehydes and several quinoline-2-carboxaldehydes via Knoevenagel condensation. The novel compounds were characterized by H-1 NMR, C-13 NMR, mass, IR, and UV-visible spectral data and elemental analyses. d.c. and a.c. conduction properties of the compounds were investigated in the frequency range of 40-10(5) Hz and temperature range 295-440 K. The d.c results showed an activated conductivity dependence on temperature for all films. Obtained data reveal that a.c. conductivity obeys the relation sigma(ac)(omega) = A omega(s) and exponent s is found to decrease by increasing temperature. The analysis of the a.c. conduction data showed that the CBH model is the dominant conduction mechanism for the electron transport in the films. Gas sensing properties of the films for the volatile organic compounds (VOCs) were also investigated in the same temperature range. Maximum sensitivity to VOCs was observed at around 360 K for compound 6.
Keywords: CONDENSATION; Chemistry